Ethnic differences in calcium, phosphate and bone metabolism. Issue 2 (May 2014) - Redmond, J.; Jarjou, L. M. A.; Zhou, B.; Prentice, A.; Schoenmakers, I.
<x content-type="archive" xml:space="preserve">Abstract</x> The prevalence of osteoporosis and the incidence of age-related fragility fracture vary by ethnicity. There is greater than 10-fold variation in fracture probabilities between countries across the world. Mineral and bone metabolism are intimately interlinked, and both are known to exhibit patterns of daily variation, known as the diurnal rhythm (DR). Ethnic differences are described for Ca and P metabolism. The importance of these differences is described in detail between select ethnic groups, within the USA between African-Americans and White-Americans, between the Gambia and the UK and between China and the UK. Dietary Ca intake is higher in White-Americans compared with African-Americans, and is higher in White-British compared with Gambian and Chinese adults. Differences are observed also for plasma 25-hydroxy vitamin D, related to lifestyle differences, skin pigmentation and skin exposure to UVB-containing sunshine. Higher plasma 1, 25-dihydroxy vitamin D and parathyroid hormone are observed in African-American compared with White-American adults. Plasma parathyroid hormone is also higher in Gambian adults and, in winter, in Chinese compared with White-British adults. There may be ethnic differences in the bone resorptive effects of parathyroid hormone, with a relative skeletal resistance to parathyroid hormone observed in some, but not all ethnic groups. Renal mineral excretion is also influenced by ethnicity; urinary Ca (uCa) and urinary P (uP) excretions are lower in African-Americans compared with White-Americans, and in Gambians compared with their White-British counterparts. Little is known about ethnic differences in the DR of Ca and P metabolism, but differences may be expected due to known differences in lifestyle factors, such as dietary intake and sleep/wake pattern. The ethnic-specific DR of Ca and P metabolism may influence the net balance of Ca and P conservation and bone remodelling. These ethnic differences in Ca, P and the bone metabolism may be important factors in the variation in skeletal health.